Cortical differences in diverticular disease and correlation with symptom reports. Issue 7 (2nd February 2018) - Pitiot, A.; Smith, J. K.; Humes, D. J.; Garratt, J.; Francis, S. T.; Gowland, P. A.; Spiller, R. C.; Marciani, L.
Abstract: Background: Recent studies have shown that the brain of patients with gastrointestinal disease differ both structurally and functionally from that of controls. Highly somatizing diverticular disease (HSDD) patients were also shown to differ from low somatizing (LSDD) patients functionally. This study aimed to investigate how they differed structurally. Methods: Four diseases subgroups were studied in a cross‐sectional design: 20 patients with asymptomatic diverticular disease (ADD), 18 LSDD, 16 HSDD, and 18 with irritable bowel syndrome. We divided DD patients into LSDD and HSDD using a cutoff of 6 on the Patient Health Questionnaire 12 Somatic Symptom (PHQ12‐SS) scale. All patients underwent a 1‐mm isotropic structural brain MRI scan and were assessed for somatization, hospital anxiety, depression, and pain catastrophizing. Whole brain volumetry, cortical thickness analysis and voxel‐based morphometry were carried out using Freesurfer and SPM. Key Results: We observed decreases in gray matter density in the left and right dorsolateral prefrontal cortex (dlPFC), and in the mid‐cingulate and motor cortex, and increases in the left (19, 20) and right (19, 38) Brodmann Areas. The average cortical thickness differed overall across groups ( P = .002) and regionally: HSDD > ADD in the posterior cingulate cortex ( P = .03), HSDD > LSDD in the dlPFC ( P = .03) and in the ventrolateral PFC ( P < .001). The thickness of the anterior cingulate cortex and of the mid‐prefrontal cortex were also found to correlate with Pain Catastrophizing (Spearman's ρ = 0.24, P = .043 uncorrected and Spearman's ρ = 0.25, P = .03 uncorrected). Conclusion & Inferences: This is the first study of structural gray matter abnormalities in diverticular disease patients. The data show brain differences in the pain network. Abstract : Structural brain differences were investigated for the first time in Diverticular Disease (DD) patients using magnetic resonance imaging. The structural brain differences highlighted between High Somatization DD (HSDD) and Low Somatization DD (LSDD) patients (as characterized using the Patient Health Questionnaire 12, PHQ12‐SS) suggest that these patient groups differ in terms of pathophysiology.